THE EFFECT OF INCUBATION TIME ON EXCYSTATION OF EIMERIA TENELLA SPOROZOITES IN VITRO - Joko Prastowo; Mufasirin Mufasirin; Sumartono Sumartono (Jurnal Sain Veteriner, 1999)
This purpose of the research is to know the effect of incubation time on excystation of Eimeria tenella sporo-zoites in vitro.Eimeria tenella oocystes treated in clorox were broken by glass beads. Sporocystes liberated from oocys were divided in six groups (I - VI), each ghroup contained 1.68.106 sporocystes. All of the groups were treated by 0,75% taur-ocholat sodium and 0,25% trypsin. Those sporocystes were incubated at 41°C for 15, 30, 45, 60, 75 and 90 minutes respectively. The data collected was the percentage at the number of sporozoites found in each group.The result showed that the increase of the number of sporozoites was paralelly with the incubation time. The highest number of sporozoites excystation was found in the 90 minutes of incubation group.